Terikan ricih kitaran di dalam tanah disebabkan gelombang jasad - Ramli Mohamad, (1990)
Theoretical expressions and charts for obtaining the maximum cyclic shear strains due to the passage of P and S waves in an elastic isotropic halfspace are presented. Plane, cylindrical and spherical P waves, and plane and cylindrical S waves are considered. The results are presented in terms of two main parameters which can be measured, ie. peak particle velocity and P or S wave velocity in the medium. The expressions and charts are of practical value in methods of analysis that require direct use of the shear strains induced by ground vibrations, e.g. in the 'threshold strain' approach